1994
DOI: 10.1161/01.atv.14.2.275
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hormone replacement therapy on lipoprotein(a) and lipids in postmenopausal women.

Abstract: High concentrations of lipoprotein(a) [Lp(a)], an independent risk factor for atherosclerosis, cannot be managed by the usual lipid-lowering agents. It has been suggested that Lp(a) levels are related to female sex hormones. Estrogen replacement therapy makes the lipid profiles favorable for delaying atherosclerosis in postmenopausal women. The effects of the combination therapy of estrogen and progesterone on lipids are controversial. This study was designed to evaluate the effect of female sex hormones on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
38
1
1

Year Published

1996
1996
1999
1999

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(45 citation statements)
references
References 48 publications
3
38
1
1
Order By: Relevance
“…45 Hormone replacement therapy has been shown to lower Lp(a) levels in postmenopausal women. 46,47 In the present study, the difference in Lp(a) levels between cases and controls found in women but not in men may perhaps be explained by the fact that women are usually older than men when they suffer their first myocardial infarction. 44 Because there was no significant age difference between men and women in the present study, the selection bias due to rejection of individuals with previous myocardial infarction is probably greater among men than women.…”
Section: Glader Et Al C Pneumoniae and Lp(a) For Cerebral Infarctionscontrasting
confidence: 47%
“…45 Hormone replacement therapy has been shown to lower Lp(a) levels in postmenopausal women. 46,47 In the present study, the difference in Lp(a) levels between cases and controls found in women but not in men may perhaps be explained by the fact that women are usually older than men when they suffer their first myocardial infarction. 44 Because there was no significant age difference between men and women in the present study, the selection bias due to rejection of individuals with previous myocardial infarction is probably greater among men than women.…”
Section: Glader Et Al C Pneumoniae and Lp(a) For Cerebral Infarctionscontrasting
confidence: 47%
“…The previous study examining the effect of plasma Lp(a) was done in the absence of atherosclerosis, which seems to be an important contributor to the arterial thrombotic process. In addition, other studies have shown a decrease in Lp(a) with HRT 17,18 and a correlation of Lp(a) to the amount of atherosclerosis. 36 Neither of these was observed in this study.…”
Section: Coagulation Parametersmentioning
confidence: 89%
“…11 How HRT lowers coronary heart disease risk is unclear, but evidence exists that HRT has beneficial effects on plasma lipoprotein concentrations, [12][13][14] inhibits progression of atherosclerosis, 15 inhibits arterial wall accumulation of LDL, 16 and reduces plasma Lp(a) concentrations. 17,18 However, there is still concern about the effect of HRT on thrombotic events. This concern is sufficient to direct many physicians to stop HRT in women with a history of thrombotic disease.…”
mentioning
confidence: 99%
“…A more ideal approach would be prospective study of subjects before and after therapeutic interventions aimed at altering serum Lp(a) levels. Because Lp(a) levels are mainly determined genetically 56 and there is no effective means to reduce Lp(a) levels without simultaneously affecting the levels of other lipoproteins, [57][58][59][60] such an interventional study would be difficult to perform. We have studied only those volunteers approached and willing to consent to studies on the effects of risk factors on arterial physiology, and therefore some selection bias may be present.…”
Section: Limitationsmentioning
confidence: 99%